The absence of Pitx3 results in postnatal loss of dopamine neurons and is associated with an increase in the pro-apoptotic Bcl2 factor Noxa and cleaved caspase 3 - Willemieke M. Kouwenhoven; Edward J. Robinson; Daniek Hamberg; Lars von Oerthel; Marten P. Smidt; Lars P. van der Heide (Cell Death and Disease)
Abstract Mesodiencephalic dopamine neurons (mdDA) of the substantia nigra pars compacta (SNc) and ventral tegmental area (VTA) play critical roles in regulating movement and motivation. Pitx3 is an essential transcription factor required for proper embryonic development and terminal differentiation of mdDA neurons. Although Pitx3 is expressed in every mdDA neuron, its ablation results only in the absence of the SNc, not the VTA. The developmental stage at which the loss of SNc first becomes apparent, as well as the underlying mechanism, remains elusive. Here, we demonstrate, using a Pitx3 knockout GFP knock-in mouse model, that this loss does not occur during embryogenesis but rather postnatally. Quantification of GFP expression revealed a significant reduction in the total number of dopamine neurons at postnatal day 3, but not at embryonic day 14.5, 15.5, and 18.5. Mechanistically this reduction is accompanied by an increase in the number of cleaved caspase 3-positive GFP neurons, suggesting apoptosis. In addition, RT-PCR performed on isolated GFP neurons, one day before the loss of dopamine neurons revealed a notable elevation in the expression of the pro-apoptotic BH3-only factor Noxa. Overexpression of Noxa in dopaminergic MN9D cells dose-dependently increases the level of cleaved caspase 3 and the number of propidium iodide-positive cells, indicating that Noxa expression is sufficient to induce cell death in dopamine cells. Additionally, Noxa expression in MN9D cells, combined with a Bax-inhibiting peptide, reduces the number of cleaved caspase 3-positive and propidium iodide-positive cells, further supporting apoptosis as the mechanistic form of cell death. Overall, our study provides insights into the cell death machinery implicated in the loss of dopamine neurons, which may hold relevance for diseases affected by the loss of dopamine neurons such as Parkinson’s disease, where this is a hallmark feature.